Linking Diversity–Productivity Conditions of Farming Systems with the Well-Being of Agricultural Communities - Francois, Jean R.; Nelson, Katherine S.; Burchfield, Emily K. (MDPI AG, 2024)
Agricultural diversity, productivity, and human well-being have been popular topics in recent decades, partly fueled by our quest for sustainability. However, the exact nature of the interconnections among these global priorities remains an area yet to be fully understood and explored. We contribute to this literature by examining how community well-being interacts with distinct levels of diversity and productivity in cropping systems across multiple U.S. communities. Using data at the county-level from 2010 to 2019, we first analyze how well-being varies across communities that differ in their levels of crop diversity and productivity. Then, we investigate how well-being varies across both diversity–productivity characteristics and farming intensity levels. We employ mapping techniques in conjunction with descriptive statistics to uncover and visualize patterns in well-being across contexts. Study findings show a consistent pattern of high levels of well-being across most diversity–productivity categories, with the notable exception of areas that are both highly diverse and highly productive. In addition, places with substantial commercial operations, and where agriculture contributes greatly to overall GDP and employment generally appears to have higher well-being scores compared to other places. Our analysis also reveals that there is more variability in the index of community well-being within each group than across groups of counties. Overall, the results suggest that the differences in community well-being are not solely determined by agricultural indicators, such as diversity–productivity characteristics and farming intensity levels, but also depend on contextual factors, such as social infrastructure, non-agricultural job opportunities, or local economic diversification.